THE EFFECT OF SELF-REGULATED LEARNING AND SELF-AWARENESS ON SELF-LEADERSHIP AMONG STUDENTS AT EXCELLENT BRAIN TUTORING CENTER IN KABANJAHE - Elpis Brahmana; Suryani Hardjo; Salamiah Sari Dewi (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2025)
This study aims to examine the influence of self-regulated learning and self-awareness on self-leadership among students at the Excellent Brain tutoring center in Kabanjahe. The research employed a quantitative approach with a correlational design. A sample of 100 students was selected using purposive sampling. Instruments used included validated and reliable scales measuring self-regulated learning, self-awareness, and self-leadership. The regression analysis revealed that both self-regulated learning and self-awareness significantly affect self-leadership, both partially and simultaneously. These findings suggest that students' ability to manage their learning processes and recognize their personal traits plays a crucial role in developing self-leadership. The implications of this study are expected to provide valuable input for tutoring institutions in developing educational strategies that foster students' self-leadership to support academic achievement and character development.